The Establishment of Decision Tree Model in Network Traffic Incident Using C4.5 Method - Made Sudarma (Institute of Advanced Engineering and Science, 2014)
Computer network traffic is computer activity information in a network which explains interconnection between communication processes. The complexity of network traffic itself depends on the number of communication models used. The utilization of classification analyzing of network incident traffic is one of utilization forms of network traffic. The accuracy of classification model itself depends heavily on the formation of data training. The usage of C4.5 method in the establishment of decision tree in data training toward network incident traffic is with the basis to see the efficiency of decision tree formation. Wireshark tool is used as network capture tool to perform data acquisition in the formation of data training.